International Public Sector Accounting Standards Implementation in the Russian Federation - Legenkova, Margarita (International Journal of Economics and Financial Issues, 2016)
The purpose of this study is to ascertain the impact of International Public Sector Accounting Standard (IPSAS) on reliability, credibility and integrity of financial reporting in State Government administration in Russia. The article provides the rationale for developing Federal accounting standards for public the sector. The proposals formulated in the study may be useful in developing and perfecting the Federal accounting standards, in practical work of accounting organizations and educational process of higher educational institutions. The article provides a substantiation of the conclusions that the adoption of the program for Federal accounting standards development and subsequent formulation of the standards will facilitate the transition of domestic accounting to a totally new level. Keywords: federal, accounting standard, public sector JEL Classifications: N10, P41, Z23